PLACENTA PRAEVIA AND IT'S OUTCOMES IN CHILDBIRTH - Eftimova, Aleksandra (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
Placenta previa is a problem during pregnancy when the placenta fully or partially covers the opening of the uterus (cervix).  The aim of this study is to determine the incidence, obstetric risk factors, maternal mortality and morbidity and perinatal outcomes in women presented with placenta previa. A total of 100 pregnant women with placenta previa were analyzed from October 2021 to December 2022.  year. After applying the criteria for inclusion and exclusion, these women were analyzed in terms of their age, parity, gestational age and clinical characteristics in presentation, history of warning bleeding, duration of hospitalization, need for blood transfusion, period of pregnancy in childbirth and pathway of childbirth.  A total of 90% of the births were complicated by Placenta previa, including 30.0% of women over 30 years of age and 80% were multipara. 60.4% had large-scale placenta previa, 33% had previous birth by caesarean section, 6.4% had a previous abortion, 12% of the cases had postpartum bleeding and 3.7% had adherent placenta. Key words: placenta praevia, caesarian section, blood transfusion.